(3QSGdI aj GdfSH GdSJ Hjf GdMeO hGdTcQs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3HNW GdeDdas)
(3ChdgG (B:s
(3hHYO aEfc SCdJ Yf GdfSH GdSJ GdJj Hjf GdMeO hGdTcQ aGYde Cf GdMeO dZI gh GdKfGA HGddSGf Ydi GdLejd GdGNJjGQj Ydi bUO GdJYXje hGdJHLjd ShGA ef HGH GdEMSGf Ch HGH GdceGds
(3BNQgG (B:s
(3aJMUd Cf GdfSH SJI ddYehe hGdNUhU HEWdGb GKfGf ddYehe hGdNUhU ef hLg Ohf hLg hGMOI ddJQGOa hGdeSGhGIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs